The Pitfalls of a Popular Concept: Co-Production in Times of Individualization, Marketization, and De-Politicization - Eriksson, Erik Masao; Eriksson, Erik Magnus (Scandinavian Journal of Public Administration, 2023)
Co-production between public administrators and citizens has attracted renewed interest in recent years. Co-production is predominantly perceived as something desirable and is claimed to improve service efficiency and outcome and user satisfaction, at the same time as addressing democratic ideals. Drawing from interviews with public administrators and patients in a Swedish healthcare context, this paper seeks to nuance the often overly positive notion of co-production by understanding these micro-level practices as being embedded in a macro-level societal context. Theorizing the empirical material based on three features of contemporary society – individualization, marketization, and de-politicization – we argue that co-production risks placing a burden and responsibility on individual users and creating a (welfare)market in which better-off people are recruited and benefitted. In this sense, co-production may consolidate or reinforce inequalities. Through de-politicization, political issues may appear as value-free; however, as long as market-logics prevail, the welfare system and practices of co-production will, in some respects, be impotent to address crucial societal issues. Co-production as a collective practice targeting democratic standards is called for, rather than an efficiency focus, preferably by taking the recruitment of those in the greatest need seriously – scaffolded by a revitalized public service ethos of public administrators and their organizations.